Enhanced settleability and dewaterability of fungal treated domestic wastewater sludge by liquid state bioconversion process - Alam, Md. Zahangir; Fakhru’l-Razi, A. (Elsevier, 2003)
A study was conducted to evaluate the settleability and dewaterability of fungal treated and untreated sludge using liquid state bioconversion process. The fungal mixed culture of Aspergillus niger and Penicillium corylophilum was used for fungal pretreatment of wastewater sludge. The fungal strains immobilized/entrapped on sludge particles with the formation of pellets and enhanced the separation process. The results presented in this study showed that the sludge particles (pellets) size of 2–5 mm of diameter were formed with the microbial treatment of sludge after 2 days of fermentation that contained maximum 33.7% of total particles with 3–3.5 mm of diameter. The settling rate (measured as total suspended solids (TSS) concentration, 130 mg/l) was faster in treated sludge than untreated sludge (TSS concentration, 440 mg/l) after 1 min of settling time. In 1 min of settling operation, 86.45% of TSS was settled in treated sludge while 4.35% of TSS settled in raw sludge. Lower turbidity was observed in treated sludge as compared to untreated sludge. The results to specific resistance to filtration (SRF) revealed that the fungal inoculum had significant potentiality to reduce SRF by 99.8% and 98.7% for 1% w/w and 4% w/w of TSS sludge, respectively. The optimum fermentation period recorded was 3 days for 1% w/w sludge and 6 days for 4% w/w sludge, respectively, for dewaterability test.